Intersectionality, gender, social class and the neoliberal self-governance of institutions and individuals - Kovalainen Anne (Svenska Handelshögskolan, 2022)
How do social class and gender assemblage with minority elite culture and neoliberalism? The article addresses the linking of intersectionality as a method, as a heuristic and an analytic tool.
Memories and Reflections from the Gender Research Group: 21 Years of Collaborative Action